Oxalate negative pole piece of lithium ion battery
By adopting multi-layer structure design and inorganic lithium supplementation agent in the oxalate negative electrode sheet of lithium-ion battery, the problems of lithium consumption and low conductivity in the prior art are solved, and efficient electrochemical performance and long life are achieved.
Patent Information
- Application Number
- CN202421185051.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2034-05-28
AI Technical Summary
The oxalate negative electrode sheets of existing lithium-ion batteries will produce by-products during the charging process, resulting in consumption of some lithium sources and reducing the efficiency of the first Coulomb. In addition, the traditional preparation process cannot achieve prelithiation and low conductivity.
The lithium-ion battery oxalate negative electrode sheet adopts a multi-layer structure, including a buffer layer, a lithium supplement layer, an active material layer, a conductive agent layer and a current collector layer, improves the conductivity and conductivity through wedge-shaped and gate-shaped structure design, and uses inorganic lithium supplement agents such as lithium sulfate to replace traditional organic polymer binders.
The conductivity, cycle stability and service life of the negative electrode sheet are improved, the first Coulomb efficiency is enhanced, and prelithiation is realized, solving the problem of low conductivity of oxalate materials.
Smart Images

Figure CN222734997U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of lithium ion batteries, in particular to an oxalate negative electrode sheet for a lithium ion battery. Background Art
[0002] At present, most of the negative electrode materials of lithium-ion batteries are graphite materials. With the continuous development of energy storage technology, the actual specific capacity of graphite negative electrode materials has been close to its theoretical specific capacity. It is urgent to find negative electrode materials with higher energy density and power density to adapt to the progress of science and technology. Oxalate negative electrode materials have high theoretical specific capacity, and through compounding other materials, they have very considerable adaptability and stability under higher current density. On the other hand, it has abundant reserves, is environmentally friendly, low cost, and has a relatively low charge and discharge voltage platform, which can provide a higher open circuit voltage for the entire battery. Therefore, it is considered to be a more potential next-generation lithium battery negative electrode material to replace graphite.
[0003] The preparation of traditional oxalate negative electrode sheets usually requires the use of organic polymer binders (PVDF) to bond the electrode active materials and conductive agents to the current collector, but the organic polymer binders do not provide actual capacity, which reduces the overall energy density of the battery. In addition, oxalate will form byproducts during the first charging process, thereby consuming part of the lithium source from the positive electrode material, causing a loss of part of the capacity, resulting in a relatively low first coulomb efficiency. The traditional electrode preparation process cannot achieve pre-lithiation. Utility Model Content
[0004] In order to solve the problems existing in the prior art, the utility model proposes a lithium-ion battery oxalate negative electrode plate, and the utility model adopts the following technical means:
[0005] A lithium-ion battery oxalate negative electrode plate, characterized in that it includes: a buffer layer; a lithium supplement layer, arranged below the buffer layer; an active material layer, arranged below the lithium supplement layer; a conductive agent layer, arranged below the active material layer; and a current collector layer, arranged below the conductive agent layer.
[0006] In some embodiments of the present application, the active material layer and the conductive agent layer are designed to be wedge-shaped structures, and the structural relationship between the active material layer and the conductive agent layer is an embedded structure. The top width of the wedge is 0 to 13 μm, and the bottom width of the wedge is 10 to 26 μm. The local structure of the surface of the conductive agent layer is a grid-like structure, the grid depth is 1 to 5 μm, the grid gap is 20 to 50 μm, and the surface of the grid-like structure is inclined at 100° to the horizontal plane.
[0007] In some embodiments of the present application, the thickness of the active material layer is 20-40 μm; and the active material layer is made of oxalate material.
[0008] In some embodiments of the present application, the conductive agent layer has a thickness of 0.3 to 1.5 μm.
[0009] In some embodiments of the present application, the conductive agent layer is made of any one or more of Super-P, Ketjen black and acetylene black.
[0010] In some embodiments of the present application, the buffer layer has a thickness of 2 to 3 μm.
[0011] In some embodiments of the present application, the buffer layer is made of polyvinyl butyral.
[0012] In some embodiments of the present application, the thickness of the lithium supplement layer is 0.8-6.0 μm; the lithium supplement layer is made of any one or more of lithium sulfate, lithium carbonate and lithium oxalate materials.
[0013] In some embodiments of the present application, the current collector layer is made of any one or more of electrolytic copper foil and rolled copper foil.
[0014] In some embodiments of the present application, the thickness of the current collector layer is 4.5 to 8 μm.
[0015] Compared with the prior art, the utility model has the following beneficial effects:
[0016] 1. The present application adopts an inorganic lithium supplement to replace the traditional organic polymer binder, which can effectively assist in forming a stable solid electrolyte film, increase conductivity, cycle stability and service life, and improve its first coulomb efficiency; the negative electrode plate of the present application adopts lithium sulfate to reduce the use of traditional polymer binders, and lithium sulfate has a series of advantages such as non-toxicity, safety, strong cohesion, strong adsorption, and good cation exchange, and can form a close contact with the active material layer, effectively preventing the active material from falling off during subsequent cycles, and the material has a strong absorption and release ability for lithium ions in the electrolyte, which greatly optimizes the ion transmission path and rate. The coating can also serve as a protective layer for oxalate to prevent erosion of liquid electrolytes.
[0017] 2. The oxalate negative electrode sheets prepared by the prior art cannot achieve pre-lithiation and cannot solve the problem of low electrical conductivity of the oxalate material itself. The utility model provides a lithium supplement layer. The lithium element doping in the lithium supplement layer can improve the electrical conductivity of electrons and the cation diffusion exchange capacity, thereby achieving pre-lithiation and solving the problem of low first coulomb efficiency of oxalate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the overall structure of an oxalate negative electrode sheet for a lithium-ion battery in an embodiment of the utility model;
[0019] Figure 2 It is a schematic diagram of the partial structure of a wedge-shaped conductive agent layer and a grid groove of an oxalate negative electrode plate of a lithium-ion battery in an embodiment of the utility model;
[0020] Figure 3 This is a magnification diagram of the utility model under the scheme of embodiment 1;
[0021] Figure 4 This is the first charge and discharge curve of the utility model under the scheme of Example 1;
[0022] Figure 5 This is a cycle performance diagram of the ferrous oxalate negative electrode of the utility model under the scheme of Example 1;
[0023] Explanation of the reference numerals: 1. buffer layer; 2. lithium supplement layer; 3. active material layer; 4. conductive agent layer; 5. current collector layer; 6. conductive agent layer wedge-shaped structure; 7. semicircular grid groove. DETAILED DESCRIPTION
[0024] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present utility model disclosure and to fully convey the scope of the present utility model disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments in the present utility model and the features in the embodiments can be combined with each other. The present utility model will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] A lithium-ion battery oxalate negative electrode plate, characterized in that: Figure 1 As shown, including:
[0026] Buffer layer;
[0027] A lithium supplement layer is disposed below the buffer layer, and the lithium supplement layer is made of any one or more of lithium sulfate, lithium carbonate and lithium oxalate;
[0028] An active material layer, disposed below the lithium supplement layer;
[0029] A conductive agent layer is disposed below the active material layer, and the conductive agent layer is made of Super-P, Ketjen black and acetylene black materials;
[0030] The current collector layer is arranged below the conductive agent layer.
[0031] Embodiment 1:
[0032] like Figure 1As shown, the oxalate electrode is stacked with a lithium supplement layer (2), an active material layer (3), a conductive agent layer (4) and a current collector layer (5) from top to bottom to form a main body of the electrode, and a buffer layer (1) is simultaneously coated on the outside of the main body of the electrode.
[0033] The buffer layer (1) is polyvinyl butyral (PVB) with a thickness of 2 μm, the lithium supplement layer (2) is lithium sulfate with a thickness of 2 μm, the active material layer (3) is ferrous oxalate with a thickness of 20 μm, the base of the wedge-shaped conductive agent layer (4) is 1 μm Ketjen black, the wedge height is 15 μm, the wedge top width is 5 μm, the wedge bottom width is 15 μm, the grid depth is 3 μm, the grid gap is 30 μm, the grid surface is inclined at 100°, and the current collector layer (5) is an electrolytic copper foil with a thickness of 8 μm.
[0034] Comparative Example 1:
[0035] This comparative example is a negative electrode sheet prepared by a traditional preparation method, which is as follows:
[0036] A slurry containing 60wt% ferrous oxalate material (polymer cracking carbon content is 15wt%), 30wt% conductive carbon black Super-P and 10wt% polyvinylidene fluoride PVDF (a commonly used binder) is coated on an electrolytic copper foil to prepare a ferrous oxalate negative electrode sheet with a thickness of 50μm.
[0037] Comparative Example 2:
[0038] This comparative example is a negative electrode sheet prepared by a traditional preparation method, which is as follows:
[0039] A slurry containing 80wt% ferrous oxalate material (polymer cracking carbon content is 15wt%), 5wt% conductive carbon black Super-P and 15wt% polyvinylidene fluoride PVDF (a commonly used binder) is coated on an electrolytic copper foil to prepare a ferrous oxalate negative electrode sheet with a thickness of 50μm.
[0040] The pole pieces of Example 1 and Comparative Examples 1-2 were cut into 14 mm discs and subjected to the following tests respectively, with three parallel tests being used for each test. The specific test steps are as follows:
[0041] (1) Battery assembly
[0042] First, the obtained electrode pieces are placed in a glove box filled with argon gas for battery assembly. The battery shell is CR2025, the diaphragm is polypropylene Celgard2400, the counter electrode is a metal lithium sheet, and the electrolyte is a commercial lithium-ion battery electrolyte purchased.
[0043] (2) Battery test
[0044] The battery test voltage range is 0.0-3.0V, and the charge and discharge currents are 0.1, 0.5, 1, 2, 3, 5, and 0.1C, respectively, to test the rate performance of each battery obtained above;
[0045] The battery test voltage range is 0.0~3.0V, and the charge and discharge current is 5C for 500 cycles to test the initial discharge capacity (mAhg) of each battery obtained above. -1 ), stable discharge capacity (mAhg -1 ) and first coulombic efficiency (%), the results are as follows:
[0046] like Figure 3 As shown in the figure, it is a rate test diagram of Example 1 and Comparative Examples 1-2. It can be seen from the figure that the degree of attenuation of the discharge specific capacity of Example 1 and Comparative Examples 1-2 increases with the increase of current density. Example 1 can still maintain a high discharge capacity at 0.1Ag after high current charge and discharge. -1 Restored to 935.59mAhg -1 The discharge capacity of comparative examples 1-2 is 677.46 mAh g -1 and 612.16mAhg -1 ,It can be seen that the new electrode provided in this experiment can effectively improve the conductivity and ion diffusion rate of the oxalate negative electrode.
[0047] like Figure 4 As shown in the figure, the first charge and discharge curves of Example 1 and Comparative Example 1-2 are as follows. -1 The decay rate of the first charge and discharge capacity at a current density of . The decay rates of Comparative Examples 1-2 and Example 1 are 41.91%, 43.01% and 38% respectively, and the corresponding first coulomb efficiencies are 58.09%, 56.99% and 62.00% respectively. It can be seen that the pole piece provided by the utility model can effectively improve the first coulomb efficiency of the oxalate negative electrode at a large current density.
[0048] like Figure 5 As shown in the figure, it is a long cycle charge and discharge diagram of Example 1 and Comparative Example 1-2. It can be seen from the figure that Comparative Example 1-2 and Example 1 have a high charge and discharge rate at 5Ag. -1 The stability and cycle performance at the current density of 1.28kWh. Example 1 has 1231.50 mAh g after 500 cycles at this current density. -1 The specific capacity and capacity retention rate of 82% are only 984.45 mAhg in comparative example 1-2. -1 and 545.08mAhg -1The specific capacity and capacity retention rates are 71.38% and 66.43% respectively. It can be seen that the electrode provided by the utility model can effectively improve the conductivity of the oxalate negative electrode, accelerate the electron migration rate to make the electrochemical reaction more rapid, and improve the reversible capacity of the oxalate negative electrode.
[0049] In some embodiments of the present application, Figure 2 As shown, the active material layer and the conductive agent layer are designed to be wedge-shaped structures, the wedge top width is 0 to 13 μm, and the wedge bottom width is 10 to 26 μm; the local surface structure of the conductive agent layer is a grid structure, the grid depth is 1 to 5 μm, the grid gap is 20 to 50 μm, and the surface of the grid structure is inclined at 100° to the horizontal plane.
[0050] Specifically, the prior art cannot achieve multi-directional transmission of electrons in the preparation of oxalate negative electrode sheets, and the effect of adding conductive agents is not obvious, resulting in a large electrochemical polarization phenomenon. The utility model sets a wedge-shaped conductive agent layer, which increases the contact area between the conductive agent and the oxalate active material through the characteristics of the wedge shape, shortens the diffusion path of electrons in the active material, greatly increases the electronic conductivity of the oxalate material and accelerates the electronic conversion reaction, fundamentally reducing its electrochemical polarization; and the design of the grid-shaped conductive agent layer makes the active material and the conductive agent contact more closely and firmly, avoiding the problem of the active material falling off during use, and increasing the cycle life of the battery.
[0051] Preferably, the buffer layer has a thickness of 2 to 3 μm.
[0052] Preferably, the buffer layer is made of any one or more of polyvinyl butyral (PVB), polyethylene glycol (PEG) and polyethylene oxide (PEO), with polyvinyl butyral (PVB) being the most preferred.
[0053] It should be understood that polyvinyl butyral is a product of the condensation of polyvinyl alcohol and butyraldehyde under acid catalysis. Since PVB molecules contain relatively long side chains, they have good flexibility, low glass transition temperature, high tensile strength and impact strength. PVB has excellent transparency, good solubility, good light resistance, water resistance, heat resistance, cold resistance and film-forming properties, so polyvinyl butyral is selected as the buffer layer material to improve the buffering performance.
[0054] Preferably, the thickness of the lithium supplement layer is 0.8 to 6.0 μm;
[0055] The lithium supplement layer is made of any one or more of lithium sulfate, lithium carbonate and lithium oxalate materials.
[0056] It is important to understand that the use of lithium sulfate reduces the amount of traditional polymer binders used, and lithium sulfate has a series of advantages such as non-toxicity, safety, strong cohesion, strong adsorption, and good cation exchange. According to the characteristics of lithium sulfate and existing research, it only needs a simple treatment in water to produce a uniform coating. The coating can also serve as a protective layer for oxalate to prevent erosion by liquid electrolytes.
[0057] Preferably, the active material layer has a thickness of 20 to 40 μm;
[0058] The active material layer is made of oxalate material.
[0059] Preferably, the conductive agent layer has a thickness of 0.3 to 1.5 μm.
[0060] Preferably, the conductive agent layer is made of any one or more of Super-P, Ketjen black and acetylene black.
[0061] It should be understood that Super-P is a small particle conductive carbon black that can be used in both positive and negative electrodes. It has no lithium storage function at all. It is dispersed around the active material in the form of primary aggregates of 150 to 200 nm to form a branched conductive network. Its function is to reduce battery resistance and improve ion conductivity. Acetylene black is acetylene with a purity of more than 99% obtained by decomposition and refining of by-product gas during pyrolysis of calcium carbide or naphtha (crude gasoline). It is obtained by continuous pyrolysis. Carbon black; it has high conductivity and oil absorption value, good thermal conductivity. The above-mentioned additives all have good conductive properties and can be selected according to actual conditions.
[0062] Preferably, the current collector layer is made of any one or more of electrolytic copper foil and rolled copper foil.
[0063] It should be understood that electrolytic copper foil is an important material for the manufacture of copper clad laminates (CCLs), printed circuit boards (PCBs), and lithium-ion batteries. Rolled copper foil is a product made by repeatedly rolling and annealing high-precision copper strips using the principle of plastic processing. Its thickness is usually between 4 and 100 microns and its width is usually less than 800 mm. Its ductility, bending resistance, and conductivity are all better than those of electrolytic copper foil, and its copper purity is also higher than that of electrolytic copper foil. Therefore, rolled copper foil can be selected in this application to improve ductility and conductivity.
[0064] Preferably, the current collector layer has a thickness of 4.5 to 8 μm.
[0065] Compared with the prior art, the utility model has the following beneficial effects:
[0066] 1. The present application adopts an inorganic lithium supplement to replace the traditional organic polymer binder, which can effectively assist in forming a stable solid electrolyte film, increase conductivity, cycle stability and service life, and improve its first coulomb efficiency; the negative electrode plate of the present application adopts lithium sulfate to reduce the use of traditional polymer binders, and lithium sulfate has a series of advantages such as non-toxicity, safety, strong cohesion, strong adsorption, and good cation exchange, and can form a close contact with the active material layer, effectively preventing the active material from falling off during subsequent cycles, and the material has a strong absorption and release ability for lithium ions in the electrolyte, which greatly optimizes the ion transmission path and rate. The coating can also serve as a protective layer for oxalate to prevent erosion of liquid electrolytes.
[0067] 2. The oxalate negative electrode sheets prepared by the prior art cannot achieve pre-lithiation and cannot solve the problem of low electrical conductivity of the oxalate material itself. The utility model provides a lithium supplement layer. The lithium element doping in the lithium supplement layer can improve the electrical conductivity of electrons and the cation diffusion exchange capacity, thereby achieving pre-lithiation and solving the problem of low first coulomb efficiency of oxalate.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the utility model rather than to limit it. Although the utility model is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the utility model can still be modified or replaced by equivalents, and any modification or equivalent replacement that does not depart from the spirit and scope of the utility model should be included in the scope of protection of the claims of the utility model.
Claims
1. A lithium ion battery oxalate negative electrode plate, characterized in that: include: Buffer layer; A lithium supplement layer is disposed below the buffer layer; An active material layer, disposed below the lithium supplement layer; A conductive agent layer, disposed below the active material layer; The current collector layer is arranged below the conductive agent layer.
2. The lithium-ion battery oxalate negative electrode sheet according to claim 1, characterized in that: The active material layer and the conductive agent layer are in a wedge-shaped embedded connection structure, the wedge top width is 0 to 13 μm, and the wedge bottom width is 10 to 26 μm; the local surface structure of the conductive agent layer is a grid structure, the grid depth is 1 to 5 μm, the grid gap is 20 to 50 μm, and the surface of the grid structure is inclined at 100° to the horizontal plane.
3. A lithium ion battery oxalate negative electrode sheet as claimed in claim 1 or 2, characterized in that: The active material layer has a thickness of 20 to 40 μm; The active material layer is made of oxalate material.
4. A lithium ion battery oxalate negative electrode plate according to claim 1 or 2, characterized in that: The conductive agent layer has a thickness of 0.3 to 1.5 μm.
5. The lithium-ion battery oxalate negative electrode sheet according to claim 1, characterized in that: The buffer layer has a thickness of 2 to 3 μm.
6. A lithium ion battery oxalate negative electrode sheet as claimed in claim 1 or 5, characterized in that: The buffer layer is made of polybutyral.
7. The lithium-ion battery oxalate negative electrode plate according to claim 1, characterized in that: The thickness of the current collector layer is 4.5-8 μm.